Influence of flax seeds on the reproduction rate of lactic acid bacilli when used in the experiment - Amirkhanova, Zh.; Bodeeva, R.; Akhmetova, S.; Kozhakhmetov, S.S.; Kushugulova, A.; Akhvlediani, L. (Fundamental and Experimental Biology, 2022)
When taking probiotics, probiotic bacteria do not always successfully take root in the human body, and prebiotics are used to stimulate their growth and metabolic activity. A wide range of biologically active substances of natural origin used as prebiotics is of special interest and positively impacts the probiotic bacteria. In this regard, priority is currently given to this problem in the leading scientific centers around the world. The research in the field of microbiology is acquiring special relevance: obtaining dairy products for healthy nutrition and preparations of biologically active living cultures of probiotic bacteria of a new generation with prebiotics. This article presents the study on the influence of flax seeds on the reproduction rate of lactic acid bacilli when used in the experiment. The modern microbiological methods were engaged in conducting the given experiment. MALDI-TOF MS was used to identify lactic acid bacilli. It has been found that the whole flaxseeds added into a fermentation medium for probiotic cultures stimulate cell proliferation of lactic acid bacilli Lh13, Lpl-5. This indicates some application potential for using a probiotic with some prebiotic added in the form of whole flax seeds.